THE EFFECT OF SEXUAL RELATIONSHIP AMONG SECONDARY SCHOOL STUDENT ON THEIR ACADEMIC PERFORMANCE - KUMAR ANUSHILAN (International Journal of Multidisciplinary Research and Studies, 2021)
The process of learning and establishing attitudes, beliefs, and values around sexuality and family life that occurs throughout a person's life in the context of the community, the family, and the educational institutions that they attend is what is referred to as sexuality education. This type of education is also referred to as sex education or family life education, and it is intended to meet a number of goals, including encouraging abstinence, reducing risky behaviours, improving health-seeking behaviours, delaying debut, decreasing the possible number of sexual partners, increasing condom usage, and promoting delayed sexual debut. Additionally, it is intended to raise students' awareness of sexuality and increase their understanding of it. From sexual development to reproductive health, interpersonal relationships to love and intimacy, body image to gender roles, and everything in between, this concept covers a wide range of topics, including relationships, the prevention of sexual violence, body image, gender identity, and sexual orientation. (Strasburger & Brown, 2014). [Citation needed] The impacts of modernity brought about by industry, education, exposure and immigration of many diverse cultures that were previously unknown in Nigeria and energized by the emergence of new technologies have resulted in a dramatic shift in the sexual behaviour of young people in Nigeria in comparison to what it was in previous generations. This has led to a significantly different sexual landscape among Nigeria's youth. The effect of this is that young people are at a greater risk for issues relating to their sexual and reproductive health as a consequence of this. Recent research indicates that young people in Nigeria are more likely to engage in antisocial behaviours, such as engaging in risky sexual practises, in comparison to their counterparts living in other regions of the globe (Odimegwu & Somefun, 2017).